USE OF MOLECULAR EPIDEMIOLOGY TO TRACE TRANSMISSION PATHWAYS FOR INFECTIOUS SALMON ANAEMIA VIRUS (ISAV) IN NORWEGIAN SALMON FARMING - P, Dr. Ptardik, P; Fridgousi, U; Vuljuagrain, U.A (International Journal of Multidisciplinary Research and Studies, 2021)
Infectious Salmon Anaemia (ISA) may be a disease affecting farmed Atlantic salmon, and most salmon-producing countries have experienced ISA outbreaks. The current study aimed to use epidemiological and viral sequence information to trace transmission pathways for ISA virus (ISAV) in Norwegian salmon farming. Methods The study covers a period from January 2007 to July 2009 with a comparatively high rate of ISA outbreaks, including an outsized cluster of outbreaks that emerged in Northern Norway (the North-cluster). Farms with ISA outbreaks and neighboring salmon farms (At-risk-sites) were tested for the presence of ISAV, and epidemiological information was collected. ISAV hemagglutinin-esterase (HE) and fusion (F) protein genes were sequenced and phylogenetic analyses were performed. Associations between sequence similarities and salmon population data were analyzed to substantiate possible transmission pathways. Results There was a high degree of genetic similarity between ISAV isolates within the North cluster. ISAV was detected in 12 of 28 At-risk-sites, and a high proportion of the viruses were identified as putative low virulent genotypes harboring the complete length highly polymorphic region (HPR); HPR0 of the HE protein and therefore the organic compound glutamine (Q) within the F protein at position 266. The sequences from HPR0/F (Q266) genotypes revealed larger genetic variation, lower viral loads, and lower prevalence of infection than HPR-deleted genotypes. Seaway distance between salmon farms was the sole robust explanatory variable to clarify the genetic similarity between ISAV isolates. Discussion We suggest that one HPR-deleted genotype of ISAV has spread between salmon farms within the North cluster. Furthermore, we discover that HPR0/F (Q266) genotypes are frequently present in farmed populations of Atlantic salmon. From this, we anticipate a population dynamics of ISAV portrayed by low virulent genotypes occasionally transitioning into virulent genotypes, causing solitary outbreaks or local epidemics through local transmission.